PERCEPTION OF ONLINE AND OFFLINE LEARNING AMONG MBBS STUDENTS IN A TERTIARY CARE HOSPITAL IN MANIPUR: A CROSS-SECTIONAL STUDY - MANOHAR, NEERAJ KUMAR SHARMA; RUBEE, THANGJAM; AKHAM, NGAMBA; SINGH, OINAM JOYCHANDRA (International Journal of Current Pharmaceutical Research, 2025)
Objective: The objectives of the present study were to evaluate the responses of undergraduate medical students on online and offline learning methods and to find associations between selected variables. Methods: A cross-sectional questionnaire-based study was conducted at Shija Academy of Health Sciences, Imphal-west, Manipur, with 284 Phase-2 and Phase-3 Undergraduate MBBS students. A validated, self-administered questionnaire consisting of 20 Likert-scale questions was distributed, and 227 complete responses were analyzed. Data analysis was performed using SPSS v25, employing chi-square tests for associations. Results: The majority of students preferred offline learning over online classes. Key findings include: Over 70% found offline classes easier for grasping concepts, regaining attention, and facilitating engagement and guidance. Students valued online classes for their flexibility, convenience during illness, and ability to overcome disturbances (e. g., curfews or blockades). However, 72.2% believed online classes could not replace offline learning, particularly for technical medical education requiring hands-on skills. Statistically significant associations (p<0.05) were observed between key variables, including preferences for offline interaction, learning efficiency, and the convenience of online education. Conclusion: The study underscores the complementary role of online method advocating for a hybrid approach to optimize competency-based medical education (CBME) in Manipur outcomes. Moreover, offline courses are more suitable more technical courses involving manual and practical training.